Siklus hidup dan parasitisasi parasitoid telur Ooencyrtus erionotae Ferriere (Hymenoptera: Encyrtidae) pada hama penggulung daun pisang Erionota thrax Linnaeus: Life cycle and parasitism of the egg parasitoid Ooencyrtus erionotae Ferriere (Hymenoptera: Encyrtidae) on the banana leaf roller pest Erionota thrax Linnaeus - Puspasari, Lindung Tri; Pudjianto; Manuwoto, Syafrida (Perhimpunan Entomologi Indonesia, 2025)
Erionota thrax Linnaeus (Lepidoptera: Hesperiidae) is an insect that actively attacks banana plants during the vegetative phase, particularly when new leaves begin to grow. Damage caused by E. thrax infestations can reach up to 63.14%, which falls into the category of severe damage. The use of the egg parasitoid Ooencyrtus erionotae Ferriere (Hymenoptera: Encyrtidae) is one of the methods to reduce the population of E. thrax in the field. This study aimed to examine the potential for parasitoid reproduction through the study of life cycle, demographic parameters, sex ratio, parasitization rate, and adult behavior. The research was conducted at the Laboratory of Parasitoid and Predator Bioecology, Department of Plant Protection, Faculty of Agriculture, IPB University, and at the Cikabayan Experimental Farm. The test insects were reared on host plants for breeding, and their life cycle and development were observed. Tests on the insects included adult longevity, parasitoid reproduction, and parasitism in the field. The data obtained were analyzed using analysis of variance (ANOVA), followed by Duncan’s multiple range test. The results showed that the life cycle of O. erionotae is relatively short, ranging from 13 to 15 days. The intrinsic rate of increase (r) for O. erionotae was 0.29 per day. The sex ratio (male:female) of O. erionotae in both laboratory and field conditions was female-biased, at 1:3.56. In the field, the parasitism rate of O. erionotae ranged from 16.5% to 48.67%. Based on its biological characteristics, demographic parameters, and field parasitism rates ranging from 16.5% to 48.67%, O. erionotae shows great potential for use as a biological control agent against the banana leaf roller pest E. thrax.